Sleep Loss in Resident Physicians: The Cause of Medical Errors? - Kramer, Milton (Frontiers in Neurology, 2010)
This review begins with the history of the events starting with the death of Libby Zion that lead to the Bell Commission, that the studied her death and made recommendations for improvement that were codified into law in New York state as the 405 law that the ACGME essentially adopted in putting a cap on work hours and establishing the level of staff supervision that must be available to residents in clinical situations particularly the emergency room and acute care units. A summary is then provided of the findings of the laboratory effects of total sleep deprivation including acute total sleep loss and the consequent widespread physiologic alterations, and of the effects of selective and chronic sleep loss. Generally the sequence of responses to increasing sleep loss goes from mood changes to cognitive effects to performance deficits. In the laboratory situation, deficits resulting from sleep deprivation are clearly and definitively demonstrable. Sleep loss in the clinical situation is usually sleep deprivation superimposed on chronic sleep loss. An examination of questionnaire studies, the literature on reports of sleep loss, studies of the reduction of work hours on performance as well as observational and a few interventional studies have yielded contradictory and often equivocal results. The residents generally find they feel better working fewer hours but improvements in patient care are often not reported or do not occur. A change in the attitude of the resident toward his role and his patient has not been salutary. Decreasing sleep loss should have had a positive effect on patient care in reducing medical error, but this remains to be unequivocally demonstrated.